2023
DOI: 10.1002/smll.202303340
|View full text |Cite
|
Sign up to set email alerts
|

Stone–Wales Defect in Graphene

Abstract: Abstract2D graphene the most investigated structures from nanocarbon family studied in the last three decades. It is projected as an excellent material useful for quantum computing, artificial intelligence, and next generation advanced technologies. Graphene exists in several forms and its extraordinary thermal, mechanical, and electronic properties, principally depend on the kind of perfection of the hexagonal atomic lattice. Defects are always considered as undesired components but certain defects in graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 191 publications
0
11
0
Order By: Relevance
“…2 Using Raman spectra, XRD, and S BET , we found that the NPC s and NPG s are mainly monolayer graphene with single vacancies 38 and heptagons/pentagons 39,40 such as Stone–Wales (SW) defects. 38,41–44…”
Section: Resultsmentioning
confidence: 99%
“…2 Using Raman spectra, XRD, and S BET , we found that the NPC s and NPG s are mainly monolayer graphene with single vacancies 38 and heptagons/pentagons 39,40 such as Stone–Wales (SW) defects. 38,41–44…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that these NPGs have both vacancies and grain boundaries since the I D /I D ′ values lie between those of graphene dominantly with vacancies (∼7) and grain boundaries (∼3.5). 112 The shoulder peak at ∼1150 cm −1 in the Raman spectra proves the existence of Stone-Wales (SW) defects, 5,[112][113][114][115] while the small peak at ∼2460 cm −1 can be attributed to the SW + D band.…”
Section: Nanoporous Graphene (Npg)mentioning
confidence: 99%
“…The mean square displacement (MSD) was employed to determine the bond strength and restoring forces of the nanotubes, wherein high restoring forces are associated with a low MSD, and then decrease in atomic mobility. 81 Additionally, a strong and rm bond are attributes of a lower MSD and atom mobility. The small MSD values observed across the systems indicate that the adsorption of NO 2 gas will force the structure to deform over time.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%